1992
DOI: 10.1111/j.1469-8986.1992.tb01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Salivary Cortisol in Severe Dental Anxiety

Abstract: The aim of the present study was to investigate the feasibility of saliva collection from highly anxious dental patients and to evaluate whether salivary cortisol concentrations could discriminate between 13 highly anxious dental patients and 13 non-anxious subjects. Whole mixed saliva was sampled by suction after stimulation with citric acid crystals. Salivary free cortisol levels were measured in duplicate by radioimmunoassay. Collection of saliva took 2-5 min and was not experienced as unpleasant. Salivary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 8 publications
3
25
0
1
Order By: Relevance
“…The same relation has been shown for anxiety (Benjamins et al, 1992;Curtis et al, 1978;Vedhara et al, 2003). But there are also studies that do not support the relationship between negative affect or anxiety and elevated cortisol.…”
Section: Cortisol and Fatigue/exhaustionmentioning
confidence: 76%
See 1 more Smart Citation
“…The same relation has been shown for anxiety (Benjamins et al, 1992;Curtis et al, 1978;Vedhara et al, 2003). But there are also studies that do not support the relationship between negative affect or anxiety and elevated cortisol.…”
Section: Cortisol and Fatigue/exhaustionmentioning
confidence: 76%
“…The results have revealed some support for an association between negative affect/mood and increased levels of cortisol (Buchanan et al, 1999;Smyth et al, 1998). The same relation has been shown for anxiety (Benjamins et al, 1992;Curtis et al, 1978;Vedhara et al, 2003). But there are also studies that do not support the relation of negative affect or anxiety to elevated cortisol.…”
Section: Studies Of the Hpa-axis In Response To Stressmentioning
confidence: 86%
“…Cortisol levels rise in response to negative experiences, such as dental examinations (Benjamins, Asscheman, & Schuurs, 1992), insults (Cohen, Nisbett, Bowdle, & Schwarz, 1996), and experimentally induced pain (Dixon, Thorn, & Ward, 2004), neutral experiences, such as cognitive tasks (Bohnen, Houx, Nicolson, & Jolles, 1990;Bohnen, Nicolson, Sulon, & Jolles, 1991), and positive experiences, such as parachute jumping (Cook, Read, Walker, Harris, & Riad-Fahmy, 1992; for a review, see Kirschbaum & Hellhammer, 1994). Cortisol levels also rise in response to physical exercise, peaking somewhat after the conclusion of the stressor (20-30 min after in Cook et al, 1992).…”
Section: Physiological Stressmentioning
confidence: 99%
“…Increased cortisol levels have been related to a wide range of stressful life experiences and experimental conditions, including dental ex ams (Benjamins, Asscheman, & Schuurs, 1992), parachute jumping (Cook, Read, Walker, Harris, & Ria-Fahmy, 1992), separation effects in infants (Larson, Gunnar, & Hertsgaard, 1991), attention tests with mild electric shock (Muller, Budde, & Netter, 1992), and being held hostage in Iran for 444 days (Rahe, 1990). Martin and Dobbin (1988) found that subjects who have relatively low scores on sense-of-humor scales have a stronger negative relationship be tween daily hassles and S-IgA levels chan do other subjects.…”
Section: Cortisolmentioning
confidence: 99%